Body fluid status and physical demand during the Giro d`Italia - Pollastri, L.; Lanfranconi, F.; Tredici, G.; Schenk, K.; Burtscher, M.; Gatterer, H. (Research in Sports Medicine, 2016)
The aim of the study was to investigate changes in hydration status by means of bioelectrical impedance vector analyses (BIVA) and to assess its influence on power output and rating of perceived exertion (RPE) during the Giro d`Italia 2014. Daily bioelectrical impedance analysis were performed on 9 professional road cyclists (age: 28.2 ± 4.7yr, height: 176.0 ± 5.5 cm, weight: 64.7 ± 3.4 kg) during the race. Additionally, body weight, RPE, and power output were recorded throughout the race. Impedance vectors shortened during the race, whereas body weight remained unchanged at the end of the tour when compared to pre-tour. Vector changes were not related to power output or RPE. The shortening of the BIVA vector indicates that fluid gain occurred during the Giro d`Italia. This fluid gain was not reflected by body weight measurements and might be mainly attributed to muscle edema and/or haemodilution. Furthermore, power output and RPE, mostly depending on team tactic, were not affected by the body water increases.